(untitled) (Revista de Medicina Clinica, 2025)
DRESS syndrome is a drug reaction with eosinophilia and systemic symptoms with an estimated incidence of 1 in 1,000 to 10,000. The case of a 42-year-old female who was admitted with a generalized dermatosis that evolved into acute liver failure, identified as DRESS syndrome, progressing to acute heart failure with the need for orotracheal intubation; She had a 40 day hospital stay, where she evolved favorably with normalization of liver enzymes. The objective of this case is the recognition of the syndrome for proper management and reduction of morbimortality.